2002
DOI: 10.1016/s0378-1097(02)00860-1
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of tetracyanonickelate (II) by Cryptococcus humicolus MCN2

Abstract: A new yeast strain capable of degrading free and metallocyanides was isolated from coke-plant wastewater. The isolated strain designated MCN2 was identified as Cryptococcus humicolus by 26S rDNA sequencing and phylogenetic analysis. During growth of the isolate with KCN as a sole nitrogen source, formamide and formic acid were found as transient intermediates by [13 C]nuclear magnetic resonance analysis and ammonia accumulated as a final product in the culture medium. The strain MCN2 could degrade high concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 19 publications
3
17
1
Order By: Relevance
“…Many previously published reports pointed out the failure in detecting ammonia accumulation due to immediate consumption of ammonia for growth of microorganisms (Kunz et al 1992;Barclay et al 1998;Kwon et al 2002;Kao et al 2003). In contrast, the transient build-up of ammonia in the present study, which was also observed by Harris & Knowles (1983), indicated that the rate of ammonia degradation was much slower in comparison to that of the rate of formation of ammonia.…”
Section: Resultscontrasting
confidence: 68%
See 4 more Smart Citations
“…Many previously published reports pointed out the failure in detecting ammonia accumulation due to immediate consumption of ammonia for growth of microorganisms (Kunz et al 1992;Barclay et al 1998;Kwon et al 2002;Kao et al 2003). In contrast, the transient build-up of ammonia in the present study, which was also observed by Harris & Knowles (1983), indicated that the rate of ammonia degradation was much slower in comparison to that of the rate of formation of ammonia.…”
Section: Resultscontrasting
confidence: 68%
“…Formate was not detectable in the biodegradation medium after 18 h of incubation which was presumably due to the action of formate dehydrogenase converting formate to carbon dioxide in the active growth system (Barclay et al 1998;Kwon et al 2002). Formamide was not detected in the culture broth during the whole period of KCN degradation.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations